(untitled) (Research, Society and Development, 2018)
The present article deals with public policies in the treatment and correct destination of plastic waste in Portugal, and the consequences that this waste can provoke in the seas where the destination of the great part is after the use. Plastic in Portugal is one of the items with the lowest recycling rate in the five characteristics of urban household waste, behind many European Community countries that have an index of more than 42% presented by the Portuguese, according to Green Point, 2018. The article also addresses the best treatment of this waste and how it should be harnessed to generate employment and income for thousands of people, rather than being landfill or thrown across the rivers.